1998
DOI: 10.1038/bjc.1998.388
|View full text |Cite
|
Sign up to set email alerts
|

Effective treatment of cutaneous and subcutaneous malignant tumours by electrochemotherapy

Abstract: Effective treatment of cutaneous and subcutaneous malignant tumours by electrochemotherapy LM Mir', LF Glass23, G Sersa4, J Teissi65, C Domenge6, D Miklavdid7, MJ Jaroszeski38, S Orlowski9, DS Reintgen38, Z Rudolf4, M Belehradek6, R Gilbertl0, M-P Rols5, J Belehradek Jr', JM Bachaud", R DeConti23, B Stabuc4, M Cemazar4, P Coninx'2 and R Heller38 The application of electric pulses to the patients was safe and well tolerated. An instantaneous contraction of the underlying muscles was noticed. Minimal adverse sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
237
0
19

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(260 citation statements)
references
References 22 publications
4
237
0
19
Order By: Relevance
“…22 Moreover, because of the antitumour efficacy of this approach, clinical trials were rapidly performed. 23,24 This approach was termed electrochemotherapy, and the pulse conditions, used in almost all the published clinical trials, [25][26][27] were eight identical square wave pulses of 100 ms and 1300 V/cm at a repetition frequency of 1 Hz using external electrodes (transcutaneous pulses). These trials demonstrated that it is possible to deliver in vivo electric pulses to animals and patients and they greatly facilitated the development of the in vivo DNA electrotransfer.…”
Section: In Vivo Delivery Of Electric Pulsesmentioning
confidence: 99%
“…22 Moreover, because of the antitumour efficacy of this approach, clinical trials were rapidly performed. 23,24 This approach was termed electrochemotherapy, and the pulse conditions, used in almost all the published clinical trials, [25][26][27] were eight identical square wave pulses of 100 ms and 1300 V/cm at a repetition frequency of 1 Hz using external electrodes (transcutaneous pulses). These trials demonstrated that it is possible to deliver in vivo electric pulses to animals and patients and they greatly facilitated the development of the in vivo DNA electrotransfer.…”
Section: In Vivo Delivery Of Electric Pulsesmentioning
confidence: 99%
“…Indeed, (a) external electric fields generate changes in the transmembrane voltage and, under appropriate conditions, provoke the transient and reversible permeabilisation of the cells, in vitro as well as in vivo and (b) BLM molecules do not diffuse through the plasma membrane and they enter only at the time of the cell electropermeabilisation, in amounts proportional to the external concentration at the moment of EP. Moreover, permeabilising EP can be applied locally in vivo on tumour nodules: the huge increase in the antitumour effectiveness of BLM achieved by the increase in BLM uptake is the basis of electrochemotherapy (ECT), a new way to treat solid tumours that is already under clinical evaluation (Domenge et al, 1996;Mir et al, 1998;Gehl and Geertsen, 2000;Rodriguez-Cuevas et al, 2001;Rols et al, 2002). Therefore, it seemed possible to study in vivo the cell death pathway caused by different amounts of DSB using these experimental conditions.…”
mentioning
confidence: 99%
“…Recently, it was employed in preclinical studies on animal models and also in clinical settings for delivery of chemotherapeutic drugs with very high antitumor efficiency and negligible side effects. 11,12 In addition, some recent studies have examined the use of electroporation to deliver plasmid DNA to various types of tissues in vivo, such as skin, liver, testis, brain, skeletal muscle, and tumors. 13 Various settings of electroporation were used, with no general conclusion on the optimal electrical, DNA, and environmental parameters for effective DNA transfer, especially when delivering DNA to tumors.…”
mentioning
confidence: 99%